2003
DOI: 10.1590/s1413-70542003000600015
|View full text |Cite
|
Sign up to set email alerts
|

Aproveitamento industrial do umbu: processamento de geléia e compota

Abstract: RESUMO -O umbu (Spondias tuberosa Arr. Cam.) é uma fruta nativa da Região Nordeste do Brasil. Ainda não devidamente caracterizado, particularmente no que se refere ao seu potencial para industrialização, o umbu demanda pesquisas. Atualmente, esses frutos são consumidos restritamente na região Nordeste, principalmente na forma in natura, preparados como refresco, sorvete ou "umbuzada" (polpa do umbu cozida com leite e açúcar). Objetivou-se com este trabalho adequar a tecnologia convencional de processamento de … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
5
1
11

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 1 publication
3
5
1
11
Order By: Relevance
“…Similar behavior was observed by MENDONÇA, RODRIGUES and ZAMBIAZI (2000) in the study of brown sugar in apple jellies, where the acidity contents were 0.99%. FOLEGATTI et al (2003) studied the industrial use of umbu and observed that the increase of pulp quantity, that is 50:50, in comparison to 40:60, resulted in acidity content increase of the product by 0.86% and 0.62% respectively, similar behavior was observed in the present study, which resulted in increase of acidity content of the products: 0.81% and 0.78% in the jellies 70:30 and 60:40, respectively.…”
Section: Pulp and Jellies Characterizationsupporting
confidence: 88%
See 2 more Smart Citations
“…Similar behavior was observed by MENDONÇA, RODRIGUES and ZAMBIAZI (2000) in the study of brown sugar in apple jellies, where the acidity contents were 0.99%. FOLEGATTI et al (2003) studied the industrial use of umbu and observed that the increase of pulp quantity, that is 50:50, in comparison to 40:60, resulted in acidity content increase of the product by 0.86% and 0.62% respectively, similar behavior was observed in the present study, which resulted in increase of acidity content of the products: 0.81% and 0.78% in the jellies 70:30 and 60:40, respectively.…”
Section: Pulp and Jellies Characterizationsupporting
confidence: 88%
“…MOTA (2006) studying blackberry jelly, noted that the obtained jellies pH kept at the range of 3.2 to 3.4, values close to those observed in the fruits pulp before the processing. FOLEGATTI et al (2003) in the umbu study, mentions that increases in the quantity of added pulp, i. e. 50:50 in comparison to the 40:60, resulted in pH decrease of the products, from 2.82 to 3.05, respectively, similar behavior was observed in the present study, which resulted in pH contents of the products of 4.01 and 4.13 in the jellies 70:30 and 60:40, respectively.…”
Section: Pulp and Jellies Characterizationsupporting
confidence: 87%
See 1 more Smart Citation
“…Individuals of this species are tolerated in heavily altered human landscapes (Cavalcanti et al 1996(Cavalcanti et al , 1999a. The principal product harvested from the "umbuzeiro" tree is its fruit, which can be consumed directly and is used to make juices or ice cream or is cooked with milk and sugar to make the traditional "umbuzada" (Cavalcanti et al 1999a, b;Costa et al 2001;Folegatti et al 2003). To our knowledge, there are currently no published reports focusing on cultural factors associated with the use and management S. tuberosa.…”
mentioning
confidence: 99%
“…Brasil, como o Sudeste e o Sul, bem como para o mercado externo, o que vem estimulando o aumento na sua produção (Folegatti et al 2003).…”
Section: Indolebutyric Acid and Substrates On Spondias Tuberosa Layeringunclassified